1988
DOI: 10.1182/blood.v72.6.1922.1922
|View full text |Cite
|
Sign up to set email alerts
|

The enzymes of the glycolytic pathway in erythrocytes infected with Plasmodium falciparum malaria parasites

Abstract: Enzymes of the glycolytic pathway as well as some ancillary enzymes were studied in normal red cells parasitized with Plasmodium falciparum in culture at varying parasitemias as well as in isolated parasites. The levels of all enzymes except diphosphoglycerate mutase, glucose-6- phosphate dehydrogenase, and adenylate kinase were elevated. Extreme elevations of hexokinase, aldolase, enolase, pyruvate kinase, and adenosine deaminase concentrations were noted. In most cases, electrophoretically distinct bands of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(38 citation statements)
references
References 15 publications
3
34
0
1
Order By: Relevance
“…Similar findings were reported in other parasitic infections. It has been reported that plasmodium-infected erythrocytes showed a decreased capacity of their antioxidant enzymes, including SOD (Friedman 1979;Wozencraft 1986;Erel et al 1997), CAT, GSH-PX (Greve et al 1999), G6PD (Roth et al 1988), methemoglobin reductase (Stocker et al 1985) and Vitamin E (Griffiths et al 2001).…”
Section: Free Radicals and Blood Parasitesmentioning
confidence: 99%
“…Similar findings were reported in other parasitic infections. It has been reported that plasmodium-infected erythrocytes showed a decreased capacity of their antioxidant enzymes, including SOD (Friedman 1979;Wozencraft 1986;Erel et al 1997), CAT, GSH-PX (Greve et al 1999), G6PD (Roth et al 1988), methemoglobin reductase (Stocker et al 1985) and Vitamin E (Griffiths et al 2001).…”
Section: Free Radicals and Blood Parasitesmentioning
confidence: 99%
“…1), and as the parasite is heavily dependent on glycolysis, PK deficiency may partly impair parasite replication. Infection by Plasmodium has been shown to increase glucose consumption of red cells by 50-100 fold, as well as resulting in a substantial increase in glycolytic enzyme levels (Oelshlegel et al, 1975;Roth et al, 1988b). However, as the mature red cell is no longer capable of synthesizing enzymes and stimulation of existent enzymes seems unlikely, it was postulated that this increase was resulting from the parasite.…”
Section: Pyruvate Kinase Deficiency and Malaria Protectionmentioning
confidence: 99%
“…The protective effect afforded by deficiencies in pyruvate kinase, an enzyme involved in glycolyis for provision of energy to mature erythrocytes, is presently under investigation, although, studies in mouse models hint that this indeed might be the case (Roth et al, 1988;Min-Oo et al, 2003). Additionally, mutations in erythrocyte membrane proteins such as erythrocyte band 3 protein, ankyrin, spectrin and glycophorin C have also been shown to confer protection against malaria (Genton et al, 1995;Allen et al, 1999;Gallagher et al, 2004).…”
Section: Genetic Resistancementioning
confidence: 99%